2009
DOI: 10.1007/s10533-009-9381-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant-soil interactions and acclimation to temperature of microbial-mediated soil respiration may affect predictions of soil CO2 efflux

Abstract: It is well known that microbial-mediated soil respiration, the major source of CO 2 from terrestrial ecosystems, is sensitive to temperature. Here, we hypothesize that some mechanisms, such as acclimation of microbial respiration to temperature and/or regulation by plant fresh C inputs of the temperature sensitivity of decomposition of soil organic matter (SOM), should be taken into account to predict soil respiration correctly. Specifically, two hypotheses were tested: (1) under warm conditions, temperature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 68 publications
(56 reference statements)
1
22
0
Order By: Relevance
“…Researchers have previously suggested that acclimation of soil microbes (Bradford et al, 2010;Crowther and Bradford, 2013;Malcolm et al, 2008;Tucker et al, 2013;Yuste et al, 2010), shifts in microbial community composition (Luo et al, 2014;Treseder et al, 2016;Wei et al, 2014) Any combination of these mechanisms could have influenced the temporal trends in soil respiration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have previously suggested that acclimation of soil microbes (Bradford et al, 2010;Crowther and Bradford, 2013;Malcolm et al, 2008;Tucker et al, 2013;Yuste et al, 2010), shifts in microbial community composition (Luo et al, 2014;Treseder et al, 2016;Wei et al, 2014) Any combination of these mechanisms could have influenced the temporal trends in soil respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms could drive this pattern by altering microbial C use as warming proceeds (Allison et al, 2010b;Bradford et al, 2008;Frey et al, 2013;Pritchard, 2011 al., 2012; Sierra et al, 2010). These include acclimation of individual microbes (Allison et al, 2010b;Crowther and Bradford, 2013;Malcolm et al, 2008;Tucker et al, 2013;Yuste et al, 2010), shifts in microbial communities (Bárcenas-Moreno et al, 2009;Luo et al, 2014;Rousk et al, 2012;Treseder et al, 2016;Wei et al, 2014), and evolutionary adaptation of microbial populations to higher temperatures (Romero-Olivares et al, 2015). In addition, labile C pools in the soils could become depleted owing to higher microbial activity (Bradford et al, 2008;Eliasson et al, 2005;Kirschbaum, 2004;McHale et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The results observed in our study may be primarily attributed to C substrate availability limitation. Previous studies have clearly demonstrated the critical role of C substrate inputs in regulating soil respiration and its temperature sensitivity of SOM decomposition (Gershenson et al, 2009;Curiel Yuste et al, 2010). The organic matter inputs into the soils come primarily from plants through two sources, including rhizosphere labile C supplies (e.g., root exudation) and litter inputs (Wan and Luo, 2003;Högberg and Read, 2006).…”
Section: Warming Effects On Soil Co 2 Effluxmentioning
confidence: 99%
“…More importantly, the contribution of root exudates to substrate availability was relatively limited because all of the experimental small plants were seedlings younger than 9 years old in 2011. As a result, continuous soil warming tends to deplete the pool of labile SOC over the short-term period and may create a negative feedback that reduces subsequent soil CO 2 efflux over time in the two species plots (Hartley et al, 2007;Curiel Yuste et al, 2010). However, it should be stressed here that the variations in soil CO 2 efflux may be also affected by photosynthesis and above-ground plant growth (Pumpanen et al, 2012), because a substantial proportion of soil CO 2 efflux originates directly from root and rhizosphere respiration using recent photosynthate (Kuzyakov and Gavrichkova, 2010).…”
Section: Warming Effects On Soil Co 2 Effluxmentioning
confidence: 99%
“…Acclimation of soil respirations has also been found (Oechel et al, 2000;Luo et al, 2001;Melillo et al, 2002;Curiel Yuste et al, 2010). Luo et al (2001) indicated the temperature sensitivity of soil respiration (Q10) decreases under warming, and increases at low temperatures through acclimation.…”
Section: Temperature Effects On Carbon Fluxesmentioning
confidence: 94%